Mangrove community structure in the waters of the Beladeng River Estuary, Dompak Village, Tanjungpinang - Zulfi Ardiansyah; Dedy Kurniawan; Susiana Susiana (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
The waters of the Beladeng River Muara is one of the areas in the Dompak Tanjungpinang Sub-District which has quite large potential for mangrove ecosystems. To maintain the condition of the mangrove ecosystem, it is necessary to know the structure of the mangrove community itself. The purpose of this study was to determine the types of mangroves and the structure of the mangrove community which includes the level of species density, species frequency, species closure, importance value index and mangrove canopy cover in the waters of the Beladeng River estuary, Dompak Tanjungpinang Village. This research was conducted in April-December 2022 using the Purposive Sampling method with 3 stations. In observing the mangrove ecosystem using the Transect Line Plot method measuring 10x10 m2. Based on the results of the study, there were 3 types of mangroves found, namely Rhizophora apiculata, Xylocarpus granatum, and Brugueira gymnorhiza. Meanwhile, the mangrove community structure obtained the highest density at station 3 with a value of 4733.34 ind/ha. At station 1, the types of Rhizophora apiculata and Xylocarpus granatum received the same frequency values, and the highest IVI was achieved by Xylocarpus granatum. At station 2 the highest species frequency values were found in 2 species, namely Xylocarpus granatum and Rhizophora apiculata, and the highest IVI was Rhizhopora apiculata. For station 3, the 3 types of mangroves got the same type frequency value, and the highest IVI was achieved by Rhizophora apiculata. Meanwhile, the highest percentage of mangrove canopy cover was found at station 1 with good and very dense categories.